Environmental Protection In The Light Of Prophetic Traditions - Garba, Ahmad (Civilization Research: Journal of Islamic Studies, 2025)
The Prophetic Sunnah has urged the protection of  environment and forbade   it with anything, because damage is forbidden in Islam in all its forms and manifestations, just as the Prophet, may God’s prayers and peace be upon him, commanded to stop and remove harmful things from the roads, and commanded to be cleaned  because the Creator is beautiful and loves beauty, and as the purified Sunnah focused on Great interest in planting and afforestation, the human relationship with the surrounding universe is based on the basis of harnessing and empowerment, as Ibn Abbas said: And harnessing necessitates empowerment, and the condition for this empowerment is the achievement of the principle of succession, so it is necessary to have sublime directives to direct human behavior in dealing With this planet, which is the seat of the human caliphate,  it is not surprising then that we find that the Sunnah of the Prophet celebrates the resources of the environment, disciplines man with a rational environmental system, and precedes human systems to preserving the environment in the best way and the highest law. On this basis, this paper aims to shed light on the issue of environmental protection in the light of the purified Prophet's Sunnah, and its justifications in this modern era. The researcher used the descriptive approach; This is done by following the scientific materials on the importance of the environmental protection and society on the Islamic perspective, especially with regard to the noble prophetic sayings, which are considered the second source of Islamic law. The focus of this study is to discuss how significance Islam has given towards environmental protection in the light of prophetic traditions. the study concluded that Islam is the only religion that encourages man to protect himself and his environs at the same time without discrimination or prejudice.